Atomic-scale microstructure of metal halide perovskite - Rothmann, M (University of Oxford, 2020)
The data contained herein contains information about the microscopic properties of organic-inorganic lead iodide perovskites, mainy focusing on FAPbI3, but also MAPbI3. The data exists in the form of a combination of micrographs obtained using LAADF STEM, strain maps and line profiles obtained using the Strain++ software package, image intensity simulations obtained with the Mustem software package, and a crystal model generated with CrystalMaker. The micrographs exist in both the raw dm3 file format, which can be opened using the free Digital Micrograph software, and the corresponding images, in tif format. The strain maps are composed of tif files containing the strain as black/white intensity images, and intensity line profiles are composed of txt files. The data values in the line profile files are separated by the pixel size in the corresponding micrographs. The cmdx crystal files can be opened using CrystalMaker and the same information is found in a crystal coordinate file, which can be opened using the free Vesta software.